2015
DOI: 10.1016/j.jfda.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antiacetylcholinesterase activities of Sorbus torminalis (L.) Crantz (wild service tree) fruits

Abstract: In this study, the antioxidant and antiacetylcholinesterase activities of Sorbus torminalis (L.) Crantz fruits were evaluated. Total phenolic and flavonoid compounds, 2,2'-azino-bis (3-ethylbenzothioazoline-6-sulfonic acid), 2,2'-diphenyl-1-picrylhydrazyl, and superoxide anion radicals scavenging activities and ferric-reducing antioxidant power of water, ethyl acetate, acetone, and methanol extracts were determined for the measurement of the antioxidant activity. Quercetin and α-tocopherol were used as standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 33 publications
3
38
0
4
Order By: Relevance
“…Nowadays, the search for new sources of effective acetylocholinoesterase inhibitors for the treatment of neurodegenerative disorders such as Alzheimer's disease is extremely important, as acetylcholinesterase catalyzes hydrolysis of a neurotransmitter acetylcholine that terminates signaling events across cholinergic synapses, including those of neuromuscular functions. Some studies suggest that dietary supplements with antioxidants and free radical scavengers may display benefits in slowing the mild cognitive impairment of Alzheimer's disease [49]. Our results for anti-AChE enzymes were similar, and the roots of D. fullonum L. exhibited stronger inhibitory effect against AChE than leaves (47.14 ± 0.05 vs. 43.89 ± 0.03%, respectively).…”
Section: Antioxidant and Antiacetylcholinesterase Activitysupporting
confidence: 72%
See 1 more Smart Citation
“…Nowadays, the search for new sources of effective acetylocholinoesterase inhibitors for the treatment of neurodegenerative disorders such as Alzheimer's disease is extremely important, as acetylcholinesterase catalyzes hydrolysis of a neurotransmitter acetylcholine that terminates signaling events across cholinergic synapses, including those of neuromuscular functions. Some studies suggest that dietary supplements with antioxidants and free radical scavengers may display benefits in slowing the mild cognitive impairment of Alzheimer's disease [49]. Our results for anti-AChE enzymes were similar, and the roots of D. fullonum L. exhibited stronger inhibitory effect against AChE than leaves (47.14 ± 0.05 vs. 43.89 ± 0.03%, respectively).…”
Section: Antioxidant and Antiacetylcholinesterase Activitysupporting
confidence: 72%
“…Therefore, we suppose the observed effects were due to phenolic acids or iridoids or other chemical constituents, including triterpene saponins and alkaloids identified in the roots of D. asper [15]. Other research [49] also shows that many plants rich in natural antioxidants have been proposed as alternative therapeutic agents for Alzheimer's disease. Ji et al [26] showed that some iridoids isolated from the roots of D. asper exhibited a moderate neuroprotective activity against Aβ 25-35 -induced cell death in PC12 cells.…”
Section: Antioxidant and Antiacetylcholinesterase Activitymentioning
confidence: 92%
“…When compared with other fruit species, Sorbus fruits have higher or similar antioxidative activity like plums, which have 5.87 to 29.19 mM trolox/kg (Kaulmann and others ) or other different fruit species 0.58 to 15.57 mM Trolox/kg (Chen and others ). It has been reported that Sorbus fruits could contribute to the health advantages in the everyday diet, due to its antioxidant possessions and nutrients (Hasbal and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study on Sorbus torminalis species [27] found 19150 mg/kg GAE total methanolextractable phenolic compounds, in frozen fruits.…”
Section: Methodsmentioning
confidence: 96%